Quantifying blue, green, and gray water footprints in a mixed land use urban catchment for sustainable urban water management - Maranan, Czarina; Cruz, Gil; Santos, Franz (Frontiers in Water, 2025)
Urbanization and climate change significantly worsen water quality and quantity issues, heightening the urgency to address the foregoing concerns in relation to sustainable urban water management. Water Footprint Accounting (WFA) provides a novel and holistic lens for urban water management by quantifying blue, green, and gray water footprints. Unlike conventional assessments that focus only on withdrawals, WFA captures both consumption and pollution, offering a more integrated view of sustainability. This study applies WFA to the University of the Philippines—Diliman campus, using adapted numerical methods from established literature. The approach highlights hidden water dependencies, identifies critical hotspots, and demonstrates the potential of WFA as a decision-support tool for building water-resilient campus. A modified WFA spreadsheet tool was developed to automate the calculation of the blue, green, and gray water, which was then used for UP Diliman. The calculated water footprint (WF) of UP Diliman was mapped, revealing a spatial representation of the WF and WF hotspots. The results revealed that the highest total footprint was the gray water footprint (WF) of stormwater, amounting to 146,048,674 m3/year, primarily associated with suspended solids from eroded ground surfaces during rainfall events. In contrast, the lowest footprint was the blue WF of rainwater at 1,240,989 m3/year. Spatial mapping of water footprints revealed hotspots that serve as indicators of urban characteristics: blue and gray WF hotspots in highly developed areas, and green WF hotspots in zones with significant evapotranspiration. These insights highlight hidden water dependencies, identify critical pressure points, and underscore the need for future developments to integrate water-saving technologies and Low Impact Development (LID) practices. Overall, this study demonstrates how WFA can be applied as an evidence-based decision-support tool for managing and improving urban water systems in mixed land-use settings.